Plasma Osteopontin Correlates with Glycemic Control in Type 2 Diabetes Mellitus Patients - Maria Diah Pramudianti; Briggite Rina Aninda Sidharta; Josua Sinambela; Medityas Winda Krissinta (Indonesian Association of Clinical Pathologist and Medical laboratory, 2021)
Diabetes Mellitus (DM) is a metabolic disease characterized by hyperglycemia due to abnormal secretions and/or insulin activity. Osteopontin (OPN) is an important component of inflammation and insulin resistance, and vitamin D decreases insulin resistance. This study aimed to analyze the correlation between OPN and glycemic control and total 25-OH vitamin D in type 2 DM. An observational analytic study with a cross-sectional approach was performed in Dr. Moewardi Hospital, Surakarta, from May to September 2018. Plasma OPN levels were measured by a sandwich enzyme immunoassay kit from Elabscience 96T Human OPN (USA), and a total of 25-OH vitamin D was evaluated using the ELFA method from Biomerieux SA (France). Data were tested by Pearson correlation (r). Type 2 DM subjects consisted of 45 (54.2%) males and 38 (45.8%) females, 36 (43.45%) well- and 47 (56.65%) poorly-controlled. The average age was 56.81±9.76 years old. The mean of OPN level in poorly-controlled cases was significantly higher (20.27±3.20 ng/mL) than well-controlled ones (15.04±3.34 ng/mL) with p=0.001. There was no significant difference in total 25-OH vitamin D between well- and poorly-controlled groups (19.84±6.65 vs. 17.24±6.78 ng/mL, respectively, p=0.085). The correlation of OPN with glycemic control (fasting glucose, 2-hour post-prandial glucose, HbA1c) and total 25-OH vitamin D in all subjects with type 2 DM were r=0.241 (p=0.028), r=0.378 (p=0.0001) r=0.529 (p=0.0001) and r=-0.151 (p=0.173), respectively. This study suggested that plasma OPN level was correlated with glycemic control but not with serum total 25-OH vitamin D in type 2 DM. Further research was needed in populations of other types of DM and other research variables related to inflammation or insulin resistance.